Alternative Reimbursement Models for Health Providers in High-Performance Sport: Stakeholder Experiences and Perceptions - Hannah E. Carter; Michelle J. Allen; Liam A. Toohey; Steven M. McPhail; Michael K. Drew (SpringerOpen, 2023)
Abstract Background Value-based healthcare provider reimbursement models have been proposed as an alternative to traditional fee-for-service arrangements that can align financial reimbursement more closely to the outcomes of value to patients and society. This study aimed to investigate stakeholder perceptions and experiences of different reimbursement systems for healthcare providers in high-performance sport, with a focus on fee-for-service versus salaried provider models. Methods Three in-depth semi-structured focus group discussions and one individual interview were conducted with key stakeholders across the Australian high-performance sport system. Participants included healthcare providers, health managers, sports managers and executive personnel. An interview guide was developed using the Exploration, Preparation, Implementation, Sustainment framework, with key themes deductively mapped to the innovation, inner context and outer context domains. A total of 16 stakeholders participated in a focus group discussion or interview. Results Participants identified several key advantages of salaried provider models over fee-for-service arrangements, including: the potential for more proactive and preventive models of care; enhanced inter-disciplinary collaboration; and the ability for providers to have a deeper understanding of context and how their role aligns with a broader set of priorities for an athlete and the organisation. Noted challenges of salaried provider models included the potential for providers to revert to reactive care delivery when not afforded adequate capacity to provide services, and difficulties for providers in demonstrating and quantifying the value of their work. Conclusions Our findings suggest that high-performance sporting organisations seeking to improve primary prevention and multidisciplinary care should consider salaried provider arrangements. Further research to confirm these findings using prospective, experimental study designs remains a priority.